IMPROVING STUDENT LEARNING OUTCOMES IN GRADE 2 FINE ARTS SUBJECTS AT SD INPRES PALUPI USING THE PROJECT-BASED LEARNING (PJBL) MODEL ASSISTED BY AUDIO VISUAL MEDIA - Setia Warni; Herlina; Ilfayani (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to determine the improvement in student learning outcomes by using the project-based learning (PJBL) learning model assisted by audio-visual media in class II Fine Arts subjects at SD Inpres Palupi. The Classroom Action Research (PTK) model that will be used in this research is the Kemmis and Mc Tanggart model. From the research results in cycle I, it was obtained that completeness was 71.42% with the number of students who completed 20 people and the number who did not complete it was 8 people. Then in the results of the second cycle test, learning completeness was obtained at 92.45% with the number of students who completed it 26 people. and the number of students who did not complete was 2 out of a total of 28 students.